My nose, your nose - Walsh, Melanie (Boston : Houghton Mifflin, 2002)
Agnes and Kit compare various parts of their bodies with one another to see how they are both similar and different.
"First published in Great Britain in 2002 by Doubleday"--Colophon.
Booklist
Horn Book
School Library Journal
2.3
K-3.
Keywords: Human anatomy -- Fiction; Human body -- Fiction; Individuality -- Fiction; Human anatomy -- Fiction; Human body -- Fiction; Individuality -- Fiction